32.9k views
3 votes

x^2+3=3-x


User Atma
by
4.3k points

2 Answers

4 votes

The answer should be x = [0, -1]

User Shawnest
by
5.1k points
7 votes

Answer:

x= 0 and x = -1

Explanation:

Solving the equation:


x^2 +3 = 3-x

Adding -3 on both sides


x^2 +3-3 = 3-3-x


x^2  = -x

Rarranging


x^2 +x= 0

Solving quadratic equation using quadratic formula


x=(-b\pm√(b^2-4ac))/(2a)

where a = 1 , b =1, c= 0


x=(-1\pm√((1)^2-4(1)(0)))/(2(1))\\x=(-1\pm√(1-0))/(2)\\x=(-1\pm√(1))/(2)\\x=(-1\pm1)/(2)\\x = (-1+1)/(2) \,\,and\,\, x=(-1-1)/(2)\\x=  (0)/(2) \,\,and\,\,  x=(-2)/(2)\\x=0 \,\,and\,\, x= -1

So, x= 0 and x = -1

User DaeMoohn
by
4.7k points